PAMs inhibits monoamine oxidase a activity and reduces glioma tumor growth, a potential adjuvant treatment for glioma - Pei-Chuan Li; Shih-Yi Chen; Danzhou Xiangfei; Canquan Mao; Chieh-His Wu; Jean Chen Shih (BMC, 2020)
Abstract Background Monoamine oxidase (MAO) A catalyzes oxidative deamination of monoamine neurotransmitters and dietary amines and regulates brain development and functions. Recently, we showed that MAO A mediates the progression and migration of glioma and MAO A inhibitors reduce glioma cell growth. Glioblastoma (GBM) is a common and most malignant brain tumor which is difficult to treat. Temozolomide (TMZ) is the current standard chemotherapy for glioma, but tumors usually become resistant and recur. So far, no effective therapy for TMZ-resistant glioma is available. Natural plant antimicrobial solution (PAMs) is a Chinese herbal medicine which has been used for decades without toxicity and has multiple medical functions including anti- inflammatory effects. Here, we report the effects of PAMs on glioblastoma growth. Methods The growth of TMZ -sensitive (U251S),-resistant (U251R) human glioma cells, and mouse glioma cell line GL-26 were assessed by MTS colorimetric assay, colony formation, and cell migration assays. Male C57BL/6 mice were implanted subcutaneously or intracranial with luciferase-positive mouse glioma GL-26 cells and treated with vehicle; MAO A inhibitor clorgyline (10 mg/kg); TMZ (1 mg/kg); PAMs (48 mg/kg) alone or in combination with TMZ (1 mg/kg) for 14 days. At the end of the treatment, mice were sacrificed, MAO A catalytic activity in tumors was measured, and tumor sizes were determined by imaging and weight. Results These results show that PAMs inhibits MAO A catalytic activity in all three glioma cell lines studied U251S, U251R, and GL-26. PAMs reduced glioma growth and has greater effects in combination with low dose of TMZ than PAMS or TMZ alone in all three cell lines as shown by MTS, colony formation, and cell migration assays. Using the subcutaneous or intracranial GL-26 glioma mouse model, PAMs reduced the tumor growth and MAO A activity, similar to the MAO A inhibitor clorgyline. Combining PAMs with non-toxic dose TMZ increased survival to a greater extent than those of PAMs or TMZ alone. Conclusions This is the first study which suggests that PAMs alone or co-administration with low doses of TMZ may be a potential adjuvant to reduce the toxicity of TMZ and to abrogate drug resistance for the effective treatment of glioma.